2018
DOI: 10.1016/j.jgr.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Red ginseng monograph

Abstract: Ginseng has been traditionally used for several millennia in Asian countries, including Korea, China, and Japan, not only as a nourishing and tonifying agent but also as a therapeutic agent for a variety of diseases. In recent years, the various effects of red ginseng including immunity improvement, fatigue relief, memory improvement, blood circulation improvement, antioxidation, mitigation of menopausal women's symptoms, and anticancer an effect have been reported in clinical as well as basic research. Around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 109 publications
0
75
0
Order By: Relevance
“…The experiment was performed in triplicate and the data is expressed as the mean ± SD. Bars marked with different letters (a-d) are significantly different (p < 0.05) according to Duncan's multiple range test than ginseng (So et al, 2018), and becomes a low-molecular substance as the sugar content in the ginsenoside drops . This drop increases the bioavailability of red-ginseng, enhancing its health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiment was performed in triplicate and the data is expressed as the mean ± SD. Bars marked with different letters (a-d) are significantly different (p < 0.05) according to Duncan's multiple range test than ginseng (So et al, 2018), and becomes a low-molecular substance as the sugar content in the ginsenoside drops . This drop increases the bioavailability of red-ginseng, enhancing its health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Red ginseng is traditionally produced by steaming ginseng nine times and drying it nine times. Red ginseng is more restorative than ginseng (So et al, ), and becomes a low‐molecular substance as the sugar content in the ginsenoside drops (Lee et al, ). This drop increases the bioavailability of red‐ginseng, enhancing its health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely used as a traditional medicine because of its health benefits. Several studies have demonstrated the beneficial effects of ginseng, such as blood circulation improvement, blood cholesterol improvement, anti‐diabetic (Kang, Lee, Ahn, & Lee, ; Qi, Wang, & Yuan, ; Yuan, Kim, Kim, & Chung, ), neuroprotective activity, memory improvement, anti‐inflammatory (González‐Burgos, Fernandez‐Moriano, & Gómez‐Serranillos, ), anticancer activity (Ahuje, Kim, Kim, Yi, & Cho, ; Lee et al, ; Xu et al, ), anti‐fatigue, anti‐stress effects, immune function improvement (So, Lee, Kim, Hyun, & Han, ; Wang et al, ), and anti‐aging effects (Bjorklund et al, ). Moreover, ginseng is also known to increase vitality, health, and longevity, especially in elderly people (Yang, Ren, Zhang, & Wu, ).…”
Section: Introductionmentioning
confidence: 99%